Burundi : 2006 Article IV Consultation, Third and Fourth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Performance Criteria, Modification of a Performance Criterion, Extension of the Arrangement, and Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries-Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Burundi is emerging from more than a decade of civil conflict that started with the 1993 coup d'etat against its first elected government. Macroeconomic developments in 2005 were broadly in line with the Poverty Reduction and Growth Facility (PRGF) program, although growth was lower at about 1 percent, largely because of a poor coffee harvest and worsening drought in the north. The 2006 budget, adopted in late 2005, envisaged a drop in revenues to 18.9 percent of GDP and spending of 40.8 percent of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet